KINERJA PEGAWAI DINAS KEBAKARAN DAN PENYELAMATAN KABUPATEN BADUNG - Adhika, I Nyoman Resa; Ardianti, Putu Novia Hapsari; Putra, I Komang Trisna Eka (Jurnal Ilmiah Cakrawarti, 2025)
Low employee performance is one of the symptoms that can damage conditions in an organization. At the Badung Regency Fire and Rescue Service there are still problems related to employee performance which have an impact on organizational performance. This is because there are still obstacles related to individual characteristics, organizational characteristics and employee work discipline that still need to be improved. This research aims to determine the influence of individual characteristics, organizational characteristics and work discipline on employee performance. The location of this research is the Badung Regency Fire and Rescue Service. The population and sample amounted to 80 employees at the Badung Regency Fire and Rescue Service. Data analysis techniques use validity tests, reliability tests, multiple linear regression analysis, classical assumption tests, multiple correlation analysis, coefficient of determination analysis, F test and T test. The research results show that: (1) work discipline has a significant positive effect on employee performance, where the regression coefficient value is 0.347 and the significance value is 0.005 (2) organizational characteristics have a significant positive effect on employee performance, where the regression coefficient value is 0.373 and the significance value is 0.000 ( 3) work discipline has a significant positive effect on employee performance, where the regression coefficient value is 0.219 and the significance value is 0.000.